Effect of winter rainfall on yield components and fruit green aromas of Vitis vinifera L. cv. Merlot in California. (25th December 2013) - Mendez‐Costabel, M.P.; Wilkinson, K.L.; Bastian, S.E.P.; Jordans, C.; McCarthy, M.; Ford, C.M.; Dokoozlian, N.
Abstract Background and Aims A field trial during the 2009 and 2010 seasons evaluated the impact of winter rainfall on the main compounds responsible for green aromas in grapes and wines, 3‐isobutyl‐2‐methoxypyrazine (IBMP) and C6 compounds. These compounds are considered undesirable in grapes and wines above the threshold concentration. Methods and Results One treatment subjected vines to average rainfall, while the other excluded winter rainfall by covering the ground with a plastic tarpaulin during the entire dormant season (November to mid‐March). Irrigation for both treatments was maintained at a weekly rate of 70% of crop evapotranspiration until commercial harvest. Canopy growth, berry size and vine yield were significantly reduced by rainfall exclusion, and a significant increase in the fruit to pruning mass ratio was recorded from one season to another. Synthesis of IBMP was significantly greater in vines under normal rainfall, whereas C6 compounds were significantly different between treatments only at the end of the second season. Fruit and wine composition, mainly colour and mouthfeel compounds, were positively affected by the absence of rainfall in both years. Wine descriptive analysis showed that the lack of rainfall produced wines perceived as less green and of more intense fruit attributes in the first season. As a consequence of the reduction in vine growth, however, the same treatment produced wines less intense in fruit aromas and of inferior tannin quality in the following season. Conclusions These results show that the soil moisture level prior to budbreak affects both canopy growth and vine yield, even when irrigation is applied following budbreak. If the rainfall level is below normal, the positive effect on fruit and wine composition achieved through smaller berry size may be offset by a significant reduction in canopy growth, resulting in severely unbalanced vines, i.e. inadequate fruit to pruning mass ratio. Significance of the Study Growers aiming to minimise the level of IBMP at harvest would benefit from applying moderate deficit irrigation and nitrogen fertilisation rates and also might achieve an earlier harvest date for those vineyards where the absence of undesirable vegetal characters is considered a key harvest metric.